2020
DOI: 10.1080/13600818.2020.1839040
|View full text |Cite
|
Sign up to set email alerts
|

Under-utilised crops and rural livelihoods: Bambara groundnut in Tanzania

Abstract: Indigenous crops are often neglected in development research, largely because they are grown in particular localities and only account for modest shares of agricultural production at a national level. This article aims to rectify this neglect with respect to the Bambara groundnut using a mixed methods study of farmers in Mtwara, Tanzania. The interest is in determining the importance of the crop in local production patterns and livelihoods, as well as potential levers for improved utilisation. Using the Sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…This new approach showcases traditional farming and processing practices that were formerly unheeded or sidelined. For instance, Boulay et al (2021) reported that farmers in Tanzania produced a specific type of groundnut and used it for home consumption. The latter crop had many agronomic and nutritional advantages, but farmers did not pay much attention to this crop due to the lack of market outlets.…”
Section: Discussionmentioning
confidence: 99%
“…This new approach showcases traditional farming and processing practices that were formerly unheeded or sidelined. For instance, Boulay et al (2021) reported that farmers in Tanzania produced a specific type of groundnut and used it for home consumption. The latter crop had many agronomic and nutritional advantages, but farmers did not pay much attention to this crop due to the lack of market outlets.…”
Section: Discussionmentioning
confidence: 99%
“…Barbier, [28] reported that rural communities which depend on ecologically fragile environments face a vicious cycle of declining livelihoods, increasing ecological degradation and loss of resource commons as well as declining ecosystem services on which they depend. Therefore, in the context when yields for major crops go rancid globally, marginal crops could increase yields and food security and encouraging environmental sustainability [29].…”
Section: Natural Capitalmentioning
confidence: 99%
“…It is mostly believed that it originated from West Africa (sahelian region) from among the Bambara tribes-people very near to Timbuktu in Mali (4,6,7). It then migrated to numerous parts of Oceanian, Asian and South American countries (8,9). It has been found to have many agronomical advantages in its nature this includes a increased nutrition values, high resistance and tolerance to drought, with abilities to survive in considerably harsh and intolerable soil types (10,11,12,13).…”
Section: Introductionmentioning
confidence: 99%